الترجيح بقرينة الاختصاص عند الإمام البيهقي في كتابه السنن الكبرى - نماذج تطبيقية - المبروك, حسين إبراهيم (مجلة الاصالة, 2025)
الترجيح بقرينة الاختصاص عند الإمام البيهقي في كتابه السنن الكبرى - نماذج تطبيقية